2019
DOI: 10.1002/ags3.12296
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA in peritoneal fluid as a biomarker of peritoneal metastases from gastric cancer

Abstract: Aim: Peritoneal metastases (PM) frequently occur in patients with gastric cancer and result in a poor prognosis. Exosomes play pivotal roles in tumor metastasis through the transfer of microRNAs (miRNAs). We examined the exosomal miRNA profile in peritoneal fluids to identify novel biomarkers to reflect tumor burden in the peritoneum. Methods: Exosomes were isolated from peritoneal fluids of patients of gastric cancer with macroscopic (P1) or microscopic (P0CY1) peritoneal metastasis (PM) and comprehensive miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Theodoraki et al demonstrated that CD44v3 protein-carrying TDE are correlated with higher disease stages and lymph node metastasis; thus, TDE could potentially serve as a noninvasive biomarker of cancer progression [65]. Studies have shown that ubiquitin C-terminal hydrolase L1 (UCH-L1) promotes motility of metastatic HNSCC as well as of extracellular vesicle-mediated transfer of the viral invasive factor LMP1 [66]. Further, Kobayashi et al proved that soluble inhibitors of UCH-L1 are effective in reducing lymph node metastasis of HNSCC; therefore, soluble inhibitors of UCH-L1 offer potential forms of treatment for invasive carcinomas, including EBVpositive malignancies [67].…”
Section: Tde Promote Metastasismentioning
confidence: 99%
“…Theodoraki et al demonstrated that CD44v3 protein-carrying TDE are correlated with higher disease stages and lymph node metastasis; thus, TDE could potentially serve as a noninvasive biomarker of cancer progression [65]. Studies have shown that ubiquitin C-terminal hydrolase L1 (UCH-L1) promotes motility of metastatic HNSCC as well as of extracellular vesicle-mediated transfer of the viral invasive factor LMP1 [66]. Further, Kobayashi et al proved that soluble inhibitors of UCH-L1 are effective in reducing lymph node metastasis of HNSCC; therefore, soluble inhibitors of UCH-L1 offer potential forms of treatment for invasive carcinomas, including EBVpositive malignancies [67].…”
Section: Tde Promote Metastasismentioning
confidence: 99%
“…During the treatment, it is easy to perform a peritoneal lavage cytological examination through the intraperitoneal access port, and the results are used to determine the effects of IP chemotherapy. Recently, Ohzawa showed that the expression pattern of miRNAs in peritoneal exosomes reflects the tumor burden in the peritoneal cavity and suggested its potential as a useful biomarker in the treatment of PM [19]. Because patients with PM lack measurable lesions that are required to decide the therapy, future studies must discover reliable biomarkers reflecting tumor activity in the peritoneum.…”
Section: Resultsmentioning
confidence: 99%
“…Although these miRNAs have already been associated with invasiveness and malignancy of CRC, they had not been until now linked to locoregional recurrence or peritoneal metastasis, although differential expression of other miRNAs, such as hsa-miR-215-5p, hsa-miR-483-5p, and hsa-miR-31-5p, between liver and peritoneal metastases has already been described in CRC [ 43 ]. In gastric cancer, miR-21-5p, miR-92a-3p, miR-223-3p, and miR-324-3p detected in peritoneal fluid are also associated with peritoneal metastasis [ 44 ]. Deregulation of other miRNAs has also been described in other cancers associated with locoregional recurrence.…”
Section: Discussionmentioning
confidence: 99%